Exploring the Syndrome Differentiation and Treatment of Colorectal Cancer Based on the Yin-Yang Theory of the Yellow Emperor’s Inner Canon - Tang, Gang; Zhang, Yami (Journal of Contemporary Medical Practice, 2026)
Colorectal cancer (CRC), as one of the most common malignant tumors of the digestive tract, poses a serious threat to the health of the Chinese population and imposes a substantial burden on society. However, most existing Western medical treatment modalities are accompanied by unavoidable adverse effects. The incorporation of Traditional Chinese Medicine (TCM) interventions represents a breakthrough in the diagnosis and treatment of CRC. In TCM, there is a diversity of perspectives regarding the etiology and pathogenesis of CRC, with numerous clinical syndrome types that render syndrome differentiation challenging. Upon in-depth study of the traditional Chinese philosophical concept of Yin-Yang and the theory of Yin-Yang pathogenesis as articulated in the Yellow Emperor’s Inner Canon, the author posits that the fundamental pathogenesis of CRC is “Yin-Yang imbalance with impeded circulation.” “Circulation” constitutes the fundamental principle governing the movement of Yin and Yang; impeded circulation leads to either local Yang-heat accumulation or Yin-cold aggregation, thereby inducing the coalescence of stasis, toxin, phlegm, and turbidity, which in turn triggers tumorigenesis. It is proposed that the pathogenesis of impeded Yin-Yang circulation can facilitate clinical syndrome differentiation in CRC and enhance the precision of TCM diagnosis and treatment. Furthermore, the feasibility of discerning the Yin-Yang pathogenesis of CRC from clinical manifestations of cold and heat as well as tumor microscopic phenotypes is discussed. In terms of clinical treatment, a strategy that integrates local and systemic considerations, with a primary focus on moderating cold and heat and promoting Yin-Yang circulation, is recommended. Medication should be tailored according to the individual’s predominant Yin-Yang inclination and proportional balance, with the goal of achieving “Yin tranquility and Yang firmness” (Yin Ping Yang Mi). By adhering to “Yin-Yang” as the fundamental principle of treatment, emphasizing classical thinking, reducing the difficulty of clinical syndrome differentiation, improving therapeutic efficacy, and enhancing the quality of life for CRC patients, this approach offers new avenues for TCM-based antitumor strategies.